Biosorpsi Tanaman Puring (Codiaeum variegatum) Terhadap Emisi Timbal (Pb) Pada Kendaraan Bermotor - Nur Amalia P; Syamsidar HS; Kurnia Ramadani (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2014)
Enhancement the motorized vehicle number will be potential for air pollution in the big cities. One of the pollutant which is resulted from burning process fuel is timbale (Pb) metal. Alternative effort that is used to decrease the higher timbale (Pb) metal pollutantmaterial is with manner biosorption use puring plant (codiaeumvariegatum).The aim of this research is to know the puring plantability in absorbs Pb metal. The treatment methodis used to sprinkling plant and without sprinkling and than directly exposure to plant with period 3,6 and 9 days. The result of research that puring leaves ability can absorb Pb concentration metal between (1 until 1,5) ppm or 0,304 mg/Kg at nine days of period exposure, it order can be considered as biosorption agent Pb metal pollution.